Leaving the meristem behind: regulation of KNOX genes - Kathryn Barton, M (BioMed Central, 2001)
The mechanism by which the plant reserves some cells as pluripotent stem cells while partitioning others into differentiated leaf tissue is fundamental to plant development. New work in Arabidopsis elucidates the genetic circuitry that distinguishes meristem from leaf.